Graphene oxide wrapped individual silver nanocomposites with improved stability for surface-enhanced Raman scattering1. Issue 69 (29th July 2015) - Gao, Nan; Yang, Ting; Liu, Tao; Zou, Yu; Jiang, Jiang
<x xml:space="preserve">Abstract</x> GO coating on Ag nanoparticles enhances SERS signals and improves the long term stability of Ag.